Impact of sampling technique on the reliability of gravimetric moisture test results - Kendzierawska, Weronika; Trochonowicz, Maciej; Chachaj, Wojciech (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
Humidity is one of the basic physical characteristics of a material. Laboratory tests to determine the percentage water content of a material are relatively simple and do not require sophisticated testing equipment. The problem, however, is the reliability of partition humidity tests. During this type of testing, it is necessary to take samples from the building and transport them to the laboratory. During both of these activities, there is a loss in the mass of water contained in the sample. Changes in the humidity of the samples, associated with the need to transport them, can be minimised by using airtight containers and lowering the temperature. A much more difficult issue to address is the elimination of losses in the mass of water contained in the samples during sampling. Laboratory moisture test manuals recommend sampling by forging methods or by so-called tube drifters. Such sampling methods are intended to exclude water mass losses. In many cases, it is necessary to take a sample from quite a considerable depth or the tests concern objects of high historical value. This precludes the sampling methods recommended by the instructions. For this reason, the most commonly used sampling method, in existing facilities, is to drill a borehole and testing the borehole. During the drilling process, overheating of the borehole occurs and evaporation of water. In scientific literature and technical studies of all kinds, it is quite often suggested to take this phenomenon into account. Unfortunately, there is no information on the value of the corrections to be made. The aim of this study is to demonstrate the difference in bulk humidity measured by the laboratory method of the same samples with different sampling techniques. In addition, correction values have been determined for specific humidity ranges.